FAO agricultural services bulletin; N.139 - Cormac Cullinan (FAO, 1999)
This book provides policy-makers and law-makers with the necessary tools to evaluate the impact of existinglaw on marketing systems and to identify the changes needed to achieve the desired policy goals.